Nanovaccines against Cervical Cancer: Reliable Strategies to Circumvent Limitations of Traditional Therapeutic Vaccines - Enwa Felix Oghenemaro; Safia Obaidur Rab; Ebraheem Abdu Musad Saleh; Asmaa F. Kassem; Jasur Rizaev; Deepak Nathiya; Parjinder Kaur; M. Ravi Kumar; Karam Kadhim; Ahmed M. Hashim (Advanced Pharmaceutical Bulletin, 2025)
Cervical cancer ranks fourth in terms of diagnosis and cancer-related deaths in women worldwide. Despite the approval of prophylactic vaccines against cervical cancers, these vaccines are not able to eradicate the existing ones. Therefore, various platforms have been developed to design therapeutic vaccines against cervical cancers, including DNA/RNA-based, protein/peptide-based, vector-based, and cell-based platforms. Despite the advantages of each platform, therapeutic vaccines have displayed limited clinical benefit in patients with cervical cancer, which is partially associated with inefficient delivery of vaccine components. To address these issues, different nanoplatforms have been developed to carry cellular or molecular components of vaccines to target cells and lymphoid tissues, thus promoting the durability and potency of immune responses against tumor cells and antigens besides decreasing side effects. Moreover, nanoparticles (NPs), as adjuvants and/or carriers, provide other advantages, including sufficient antigen loading and uptake by antigen-presenting cells (APCs), adaptable antigen presentation, high immunogenicity, high stability, increased lymph node retention, and precise targeting. Thus, nanovaccines also lead us to design and develop personalized vaccines against cervical cancer. Here, we discuss platforms that have been used in clinical trials for the treatment of cervical cancer, their advantages and disadvantages, platforms for developing nanovaccines, and how they improve the therapeutic efficacy of vaccines.